Isolated Vitamin D Deficiency Is Not Associated with Nonthyroidal Illness Syndrome, but with Thyroid Autoimmunity. (12th January 2015) - Sayki Arslan, Muyesser; Topaloglu, Oya; Ucan, Bekir; Karakose, Melia; Karbek, Basak; Tutal, Esra; Caliskan, Mustafa; Ginis, Zeynep; Cakal, Erman; Sahin, Mustafa; Ozbek, Mustafa; Delibasi, Tuncay
Abstract : Aim . This study aimed to compare thyroid functions, thyroid autoantibodies, and the existence of nonthyroidal illness syndrome (NTIS) according to vitamin D level. Materials and Methods . The study included age- and BMI-matched healthy volunteers with and without vitamin D deficiency. In addition, the nonthyroidal illness syndrome status was evaluated. Results . Anti-TPO positivity was significantly more common in those with severe and moderate vitamin D deficiency, as compared to those with a normal 25(OH)D level. Furthermore, TSH levels were significantly lower in those with severe and moderate vitamin D deficiency than in those with a normal 25(OH)D level. In addition, there was a significant weak inverse correlation between anti-TPO positivity and the 25(OH)D level and a positive correlation between the TSH level and 25(OH)D level. Only 1 thyroid function test result was compatible with NTIS among the participants with moderate vitamin D deficiency; therefore the difference was not significant. Conclusions . The prevalence of thyroid autoantibody positivity was higher in those with severe and moderate vitamin D deficiency than in those with a normal 25(OH)D level. Additional large-scale studies must be conducted to determine if vitamin D deficiency plays a causal role in the pathogenesis of Hashimoto's thyroiditis and NTIS.